The Effect of Dryer Air Temperature on The Moisture Content of Cassava Flour in The Pneumatic Drying Process - Yus Witdarko (Faculty of Agriculture, Musamus University, 2018)
Drying method that is applied in flour manufacturing industry, one of which is pneumatic drying. Variable types of both the properties of the dried material and the conditions of the drying process greatly affect the quality of the results of drying. Water content is an important variable in determining the quality of flour. The purpose of this study was to find the effect of drying air temperature on the moisture content of cassava flour under the conditions of the pneumatic drying process. Drying of cassava flour at desiccant air temperatures of 145oC and 160oC with 2 drying cycles produced a moisture content of 11.3 and 8.7% wb and had fulfilled SNI for flour water content, which was a maximum of 12% wb. The higher the temperature of the drying air, the lower the moisture content.